Intrasegmental recombination as an evolutionary force of Lassa fever virus - He, Cheng-Qiang; Kong, Chao; He, Mei; Chen, Guan-Xiang; Liu, Shu-Min; Ding, Nai-Zheng (Frontiers in Microbiology, 2024)
Lassa fever (LF), caused by Lassa virus (LASV), is one of the most dangerous diseases to public health. Homologous recombination (HR) is a basic genetic power driving biological evolution.However, as a negative-stranded RNA virus, it is unknown whether HR occurs between LASVs and its influence on the outbreak of LF. In this study, after analyzing 575 S and 433 L segments of LASV collected in Africa, we found that LASV can achieve HR in both of its segments. Interestingly, although the length of S segment is less than half of L segment, the proportion of LASVs with S recombinants is significantly higher than that with L recombinants. These results suggest that HR may be a feature of LASV, which can be set by natural selection to produce beneficial or eliminate harmful mutations for the virus, so it plays a role in LASV evolution during the outbreak of LF.